Diseases of swine (Iowa State University Press, 1986)
The ideal alternative to ecology texts that tend to be too difficult for non-majors, this succinct 13-chapter, full-color textbook covers scientific principles and concepts, ecosystems, evolution, biodiversity, population ecology, and more. New to this edition for instructors is PowerLecture, a one-stop shop for lecture prep that includes everything you need to create dynamic lectures all in one place.